Angka Kelahiran dan Ketersediaan Layanan Kesehatan Ibu Bersalin - Tausiyatul Baziroh; Ririn Rizkiyah; Akrom Akrom (PT. Hasba Edukasi Mandiri, 2026)
This study analyzes the dynamics of birth rates and the availability of maternal health services in Banten Province. Based on data from 2025 to 2026, Banten's total fertility rate was recorded at 1.96 births per woman, below the national average. However, there are 38,534 pregnant women and 14,114 postpartum women who require quality health services. The collaborative MOMENTUM program successfully reduced the maternal mortality rate by 55 percent, from 214.4 to 95.7 per 100,000 live births, and expanded services from 46 to 134 health facilities. The main challenges include the suboptimal implementation of the Free Nutritious Meal program, with only 258 out of 1,081 Nutrition Service Units actively serving pregnant women, as well as data collection constraints at the sub-district level. The integration of free services and strengthening of the referral system are future projections to achieve the stunting reduction target of 16.7 percent by 2029. This study recommends data synchronization and stronger cross-sectoral collaboration.